ISOLATION AND EVALUATION OF NICKEL-TOLERANT BACTERIA FROM AQUATIC PLANT ROOTS FOR NICKEL BIOSORPTION IN LOKOJA, KOGI STATE - Ojiego, Beatrice O.; Obioh, Gloria I. B.; Odoh, Joshua A.; Madu, Josephine; Ogu, Gideon I. (FUDMA Journal of Sciences, 2025)
Nickel contamination in aquatic ecosystems poses increasing ecological and public-health risks, particularly in rapidly urbanizing riverine environments. This study aimed to isolate and evaluate nickel-tolerant bacteria associated with the roots of aquatic plants for their potential application in nickel biosorption within Lokoja, Kogi State, Nigeria. Water and root samples of Eichhornia crassipes, Nymphaea lotus, and Limnocharis flava were collected from three pollution-prone riverbank locations. Standard microbiological procedures were used for bacterial enumeration, isolation, and phenotypic characterization, while nickel tolerance was assessed using NiCl₂-supplemented media. Biosorption assays were conducted using dried bacterial biomass across varying nickel concentrations (5–20 ppm) and pH values (3–8). Data were analyzed using one-way ANOVA at p < 0.05. Four isolates: Pseudomonas putida, Pseudomonas aeruginosa, Enterobacter cloacae, and Bacillus subtilis, exhibited significant nickel tolerance (MIC > 3.0 mg/mL). P. aeruginosa demostrated the highest biosorption efficiency (84.63% at 20 ppm), with maximum removal for all isolates occurring at pH 7. Physicochemical analysis of water indicated moderate but increasing pollution downstream. These findings suggest that water plant root-associated bacteria, notably Pseudomonas spp. possess substantial potential for effective nickel bioremediation. It is therefore recommended that these isolates be further evaluated in pilot-scale bioremediation trials, particularly in resource-limited or nickel-impacted water systems.